Analisis Hubungan antara Profesionalisme Auditor dengan Pertimbangan Tingkat Materialitas dalam Proses Pengauditan Laporan Keuangan - Reni Yendrawati (Universitas Muhammadiyah Yogyakarta, Indonesia, 2006)
This study sought to determine the relationship between the professionalism of auditors as independent variables with the dependent variable is the level of materiality considerations in the process of auditing the financial statements. Respondents are professionals working in the public accounting firm in the city of Yogyakarta, both as an intern, junior auditors, senior auditors, supervisors, managers and partners. With nonprobabilitas sampling method, this research seeks to collect information from respondents available at the time of the study to provide information needed in research. Questionnaires are used as a tool to measure the variables used in the study. The hypothesis was tested using kendall tau nonparametric statistical methods to determine whether there is a relationship between the level of professionalism of the auditor's consideration of materiality in the process of auditing the financial statements. From the tests carried out showed that the auditors professionalism variables associated significantly and positively associated with variable levels of materiality considerations in the process of auditing the financial statements are indicated by = 0.570. Each dimension of professionalism of auditors, namely: dedication, social obligations, self-reliance, confidence in the regulatory profession, relationships with colleagues is significantly and positively associated with variable levels of materiality considerations. That relationship suggests that the more an auditor that has a high dedication to the profession, have a high awareness that the audit profession is a profession that is trusted by the people, has the mental attitude of self-contained, have confidence in the quality of self and peers who are equally understand the work of auditing and having relations with other professions will be able to make extensive consideration materiality levels better.